Imaging methods in the diagnosis and treatment of pancreatic cancer - Girsa, D; Weichet, J (Rozhledy v chirurgii, 2024)
Surgery is the only potentially curative treatment of pancreatic cancer. Imaging methods, especially computed tomography (CT), play an essential role in the detection and staging of pancreatic cancer. The primary CT finding determines the treatment strategy, namely the resectability of the cancer with a potentially curative outcome. Imaging (CT) assessments are important also throughout oncological treatment of the patients and after the surgery, as well. Our paper summarizes the current state of the art of computed tomography and magnetic resonance imaging in pancreatic cancer, including a structured CT report proposal in pancreatic cancer.
Keywords: magnetic resonance; počítačová rentgenová tomografie; Magnetic Resonance Imaging; magnetická rezonanční tomografie; pancreatic cancer; Pancreatic cancer; Humans; nádory slinivky břišní; computed tomography; lidé; Pancreatic Neoplasms; magnetic resonance imaging; Tomography, X-Ray Computed